Synthesis of a novel oil‐absorption resin and optimization of its performance parameters using response surface design. (4th March 2019) - Kong, Lingtong; Ma, Lei; Jin, Haibo; Hou, Jing; He, Guangxiang; Zhang, Rongyue
Abstract : A novel porous oil absorbing resin with the main monomers of stearyl methacrylate and isooctyl methacrylate was synthesized using suspension polymerization. The synthesis experiments were conducted using the response surface design method. And the influences of initiator concentration, cross‐linker concentration, and dispersant concentration were investigated. Through analyzing the second‐order polynomial mathematical models and the corresponding data, the mutual effects between these factors on the oil‐absorption performance were obtained. The response surface was used to analyze the oil (gasoline, diesel, and kerosene) absorption performance in the pure oil samples and oily water samples, respectively. The content of initiator and cross‐linker exhibited a necessary effect on the absorption of gasoline and kerosene. Moreover, the two most significant factors for diesel are the amount of initiator and dispersant. The experimental results showed that the oil‐absorbing resin synthesized under the optimized condition could achieve better oil‐absorption rate on all three oils. The absorption rates of gasoline, diesel, and kerosene are 10.14, 10.73, and 11.69 g/g, respectively, which the deoiling rate can reach closed 100% in the water sample containing gasoline and kerosene.